Nanotechnologies for Reactive Oxygen Species“Turn-On” Detection - Jiang, Hongfei; Lin, Qian; Yu, Zongjiang; Wang, Chao; Zhang, Renshuai (Frontiers in Bioengineering and Biotechnology, 2021)
Reactive oxygen species (ROS) encompasses a collection of complicated chemical entities characterized by individually specific biological reactivities and physicochemical properties. ROS detection is gaining tremendous attention. The reaction-based nanomaterials for ROS ‘turn-on’ sensing represent novel and efficient tools for ROS detection. These nanomaterials have the advantages of high sensitivity, real-time sensing ability and almost infinite contrast against background. This review focuses on appraising nanotechnologies with ROS ‘turn-on’ detection mechanism coupled with the ability for broad biological applications. We wish to highlight the weaknesses and strengths in prior sensor studies and raise some guidelines for the development of future nanoprobes.